Against Dharma : dissent in the ancient Indian sciences of sex and politics - Doniger, Wendy (Terry lectures., 2018)
An esteemed scholar of Hinduism presents a groundbreaking interpretation of ancient Indian texts and their historic influence on subversive resistance Ancient Hindu texts speak of the three aims of human life: dharma, artha, and kama. Translated, these might be called religion, politics, and pleasure, and each is held to be an essential requirement of a full life. Balance among the three is a goal not always met, however, and dharma has historically taken precedence over the other two qualities in Hindu life. Here, historian of religions Wendy Doniger offers a spirited and close reading of ancient Indian writings, unpacking a long but unrecognized history of opposition against dharma. Doniger argues that scientific disciplines (shastras) have offered lively and continuous criticism of dharma, or religion, over many centuries. She chronicles the tradition of veiled subversion, uncovers connections to key moments of resistance and voices of dissent throughout Indian history, and offers insights into the Indian theocracy's subversion of science by religion today.